Modified lithium ion sieve, membrane with separation function and preparation method and application of modified lithium ion sieve and membrane

By mixing lithium ion sieve with polyvinyl alcohol to form a modified lithium ion sieve, the existing nanofiltration membrane has solved the problem of low efficiency and poor acid and alkali resistance in magnesium-lithium separation, and achieved efficient magnesium-lithium separation and stable membrane performance.

CN119318938AActive Publication Date: 2025-01-17CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202310877768.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-17
Publication Date
2025-01-17
Estimated Expiration
2043-07-17

AI Technical Summary

Technical Problem

The existing nanofiltration membranes are inefficient in the separation of lithium ions and magnesium ions and have poor acid and alkali resistance, making it difficult to meet the needs of long-term use.

Method used

Using a modified lithium ion sieve, a film with high acid and alkali resistance and high magnesium lithium separation efficiency is prepared by mixing the lithium ion sieve with polyvinyl alcohol to form a coating layer, which is suitable for magnesium lithium separation.

Benefits of technology

It improves the separation efficiency and water flux of magnesium lithium, ensuring the stability and long-term use ability of the membrane in an acid-base environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004343953590000151
    Figure BDA0004343953590000151
  • Figure BDA0004343953590000152
    Figure BDA0004343953590000152
  • Figure BDA0004343953590000161
    Figure BDA0004343953590000161
Patent Text Reader

Abstract

The invention relates to the field of separation and purification, and discloses a modified lithium ion sieve and a membrane with a separation function as well as preparation methods and applications thereof. The modified lithium ion sieve comprises a lithium ion sieve and polyvinyl alcohol coating the lithium ion sieve, and the mass content of the polyvinyl alcohol is 0.5-5wt% relative to the mass of the modified lithium ion sieve. The modified lithium ion sieve provided by the invention has relatively good acid and alkali resistance, and when the modified lithium ion sieve is applied to a magnesium-lithium separation membrane, the separation efficiency of the magnesium-lithium separation membrane can be improved. The membrane provided by the invention has relatively good acid and alkali resistance and a stable structure, and the modified lithium ions loaded on the membrane are not easy to fall off, so that the membrane is suitable for long-term use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of separation and purification, and in particular to a modified lithium ion sieve and a membrane with separation function, and preparation methods and applications thereof. Background Art

[0002] In recent years, with the widespread application of new energy vehicles, the demand for lithium energy has gradually increased. Extracting pure lithium resources from salt lakes is currently the key way to obtain lithium resources. However, my country's salt lake brine has a high magnesium-lithium ratio (ratio of about 10-300). The radius of lithium ions and magnesium ions is very close, and lithium ions and magnesium ions have similar chemical properties, making them difficult to separate. At present, membrane separation and adsorption methods are widely used in lithium extraction from salt lakes, and the two are usually used in conjunction. In the adsorption method, the adsorbent is adsorbed in the brine, and then hydrochloric acid is used as a desorption liquid for desorption to obtain a solution containing lithium ions and a small amount of other divalent ions such as magnesium. The resulting solution is then passed through a nanofiltration membrane for further ion separation (mainly including magnesium-lithium separation). However, due to the large amount of H contained in the desorption liquid, + Therefore, the nanofiltration membrane is required to have not only good magnesium-lithium separation performance, but also good acid and alkali resistance.

[0003] However, the nanofiltration membranes that have been commercialized so far have poor permeability to lithium ions, low magnesium-lithium separation efficiency, and poor acid and alkali resistance, making them unsuitable for long-term use. Therefore, it is urgent to develop magnesium-lithium separation membranes with excellent separation performance and acid and alkali resistance. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of low magnesium-lithium separation efficiency and poor acid and alkali resistance of existing membrane products in the prior art, and to provide a modified lithium ion sieve and a membrane with separation function and their preparation methods and applications. The membrane has a thin and dense separation layer. When the modified lithium ion sieve and the membrane are used, a higher magnesium-lithium separation efficiency and a higher water flux can be obtained. The membrane also has good acid and alkali resistance and a stable structure. When the membrane is used for magnesium-lithium separation, the efficiency is higher and it is more suitable for long-term use.

[0005] In order to achieve the above object, the first aspect of the present invention provides a modified lithium ion sieve, which comprises a lithium ion sieve and polyvinyl alcohol coating the lithium ion sieve, wherein the mass content of the polyvinyl alcohol is 0.5-5wt% relative to the mass of the modified lithium ion sieve.

[0006] The second aspect of the present invention provides a method for preparing a modified lithium ion sieve, the method comprising: mixing polyvinyl alcohol and a lithium ion sieve in a solution state to obtain a modified lithium ion sieve, wherein the mass ratio of the lithium ion sieve to the polyvinyl alcohol is (0.3-5):1.

[0007] The third aspect of the present invention provides a modified lithium ion sieve prepared by the method described in the second aspect.

[0008] The fourth aspect of the present invention provides a membrane with separation function, which comprises a porous support layer, a separation layer, and the modified lithium ion sieve as described in the first aspect or the third aspect further loaded on the porous support layer and / or the separation layer.

[0009] A fifth aspect of the present invention provides a method for preparing a membrane with a separation function, the method comprising: introducing the modified lithium ion sieve as described in the first aspect or the third aspect into the process of preparing the membrane.

[0010] The sixth aspect of the present invention provides a membrane with separation function prepared by the method described in the fifth aspect.

[0011] The seventh aspect of the present invention provides the use of the membrane with separation function as described in the fourth aspect or the sixth aspect in magnesium-lithium separation.

[0012] The modified lithium ion sieve provided by the present invention has good acid and alkali resistance, and when applied to a membrane for magnesium-lithium separation, it can improve the separation efficiency of the magnesium-lithium separation membrane; in particular, according to the method for preparing a magnesium-lithium separation membrane preferably provided by the present invention, the modified lithium ion sieve is introduced when preparing a porous support layer, so that the obtained membrane can be further guaranteed to have a high magnesium-lithium separation efficiency and water flux. In addition, the membrane provided by the present invention also has good acid and alkali resistance, a stable structure, and the modified lithium ions loaded thereon are not easy to fall off, and are suitable for long-term use. DETAILED DESCRIPTION

[0013] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0014] In a first aspect, the present invention provides a modified lithium ion sieve, comprising a lithium ion sieve and polyvinyl alcohol coating the lithium ion sieve, wherein the mass content of the polyvinyl alcohol is 0.5-5wt% relative to the mass of the modified lithium ion sieve.

[0015] It can be understood that the polyvinyl alcohol coating the lithium ion sieve refers to a coating layer of polyvinyl alcohol formed on the outside of the lithium ion sieve.

[0016] The inventors of the present invention have found in their research that the modified lithium ion sieve as described above has strong acid and alkali resistance. Applying the modified lithium ion sieve to the membrane used for magnesium-lithium separation can significantly improve the magnesium-lithium separation efficiency, while also ensuring that the membrane has a high water flux and a high treatment efficiency.

[0017] According to the present invention, preferably, relative to the total mass of the modified lithium ion sieve, the mass content of polyvinyl alcohol is 0.9-2.5wt% (for example, it can be 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 2wt%, 2.2wt%, 2.5wt% and the range formed by any two of the above values ​​and the value within the range).

[0018] According to the present invention, preferably, the average thickness of the polyvinyl alcohol coating the lithium ion sieve is 1-20 nm, more preferably 2-8 nm (for example, it can be 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, and the range formed by any two of the above values ​​and the value within the range).

[0019] Within the above range, the magnesium-lithium separation efficiency is further improved when the modified lithium ion sieve is applied to the magnesium-lithium separation membrane.

[0020] According to the present invention, preferably, the average particle size of the modified lithium ion sieve is 10nm-10μm, more preferably 20-520nm (for example, it can be 20nm, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 380nm, 400nm, 420nm, 450nm, 500nm, 520nm and the range formed by any two of the above values ​​and the value within the range).

[0021] According to the present invention, preferably, the lithium ion sieve is selected from a lithium manganese oxide type lithium ion sieve and / or a lithium titanium oxide type lithium ion sieve. For example, the lithium ion sieve may be Li 1.33 Mn 1.67 O4、Li4Ti5O 12 and Li4Mn5O 12 At least one of .

[0022] According to the present invention, preferably, the weight average molecular weight of the polyvinyl alcohol is 20,000-40,000 g / mol.

[0023] In a second aspect, the present invention provides a method for preparing a modified lithium ion sieve, the method comprising: mixing polyvinyl alcohol and a lithium ion sieve in a solution state to obtain a modified lithium ion sieve, wherein the mass ratio of the lithium ion sieve to the polyvinyl alcohol is (0.3-5):1.

[0024] Through the above method, polyvinyl alcohol can be coated on the surface of the lithium ion sieve to obtain a modified lithium ion sieve. The modified lithium ion sieve obtained in this way has strong acid and alkali resistance. Applying the above modified lithium ion sieve to the membrane used for magnesium-lithium separation can significantly improve the magnesium-lithium separation efficiency, while also ensuring that the membrane has a high water flux and a high treatment efficiency.

[0025] According to the present invention, preferably, the mass ratio of polyvinyl alcohol to lithium ion sieve is (0.4-2):1.

[0026] According to the present invention, preferably, in the solution, the mass concentration of polyvinyl alcohol is 0.1-5wt% (for example, it can be 0.1wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt% and the range formed by any two of the above values ​​and the value within the range).

[0027] According to the present invention, preferably, the mixing time is 2-4h (for example, it can be 2h, 3h, 4h), and the mixing temperature is 20-40°C (for example, it can be 20°C, 22°C, 25°C, 28°C, 30°C, 32°C, 35°C, 38°C, 40°C and the range formed by any two of the above values ​​and the value within the range). Polyvinyl alcohol and lithium ion sieve can be mixed in water, and stirring can be performed during the above mixing time.

[0028] According to the present invention, preferably, the average particle size of the lithium ion sieve is 10nm-10μm, more preferably 20-500nm (for example, it can be 20nm, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 380nm, 400nm, 420nm, 450nm, 500nm, and the range formed by any two of the above values ​​and the value within the range).

[0029] According to the present invention, preferably, the lithium ion sieve is selected from a lithium manganese oxide type lithium ion sieve and / or a lithium titanium oxide type lithium ion sieve. The lithium ion sieve may be Li 1.33 Mn 1.67 O4、Li4Ti5O 12 and Li4Mn5O 12 At least one of .

[0030] According to the present invention, preferably, the weight average molecular weight of the polyvinyl alcohol is 20,000-40,000 g / mol.

[0031] According to the present invention, preferably, the method further comprises: performing solid-liquid separation on the mixed material, and drying the obtained solid phase material. The mixed material can be centrifuged. After centrifugation, the material can be washed (can be washed with distilled water 2-4 times), and ball milled to improve the dispersibility of the material (can be carried out at room temperature for 4-8 hours), and then dried. The drying time can be 8-12 hours, and the temperature can be 80-90°C.

[0032] In a third aspect, the present invention provides a modified lithium ion sieve prepared by the method described in the second aspect.

[0033] In a fourth aspect, the present invention provides a membrane with a separation function, which comprises a porous support layer, a separation layer, and a modified lithium ion sieve as described in the first aspect or the third aspect further loaded on the porous support layer and / or the separation layer.

[0034] According to a particularly preferred embodiment of the present invention, the modified lithium ion sieve is supported on a porous support layer.

[0035] According to the present invention, preferably, relative to 1g of the membrane, the loading amount of the modified lithium ion sieve is 1-100mg, more preferably 3-15mg (for example, it can be 3mg, 4mg, 5mg, 6mg, 7mg, 8mg, 9mg, 10mg, 11mg, 12mg, 13mg, 14mg, 15mg, and the range formed by any two of the above values ​​and the value within the range).

[0036] According to the present invention, preferably, the membrane with separation function comprises a substrate layer, a porous support layer and a separation layer in sequence, and the modified lithium ion sieve is loaded on the porous support layer.

[0037] According to the present invention, preferably, the thickness of the substrate layer is 30-150 μm, preferably 50-120 μm (for example, it can be 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, and the range formed by any two of the above values ​​and the value within the range); the average pore diameter is 10-25 μm; and the porosity is 15-25%.

[0038] According to the present invention, preferably, the thickness of the porous support layer is 10-100 μm, preferably 30-60 μm (for example, it can be 30 μm, 40 μm, 50 μm, 60 μm, and a range formed by any two of the above values ​​and a value within the range).

[0039] According to the present invention, preferably, the thickness of the separation layer is 80-110nm, more preferably 85-95nm (for example, it can be 85nm, 86nm, 87nm, 88nm, 89nm, 90nm, 91nm, 92nm, 93nm, 94nm, 95nm, and the range formed by any two of the above values ​​and the value within the range).

[0040] According to the present invention, preferably, the average pore size of the porous support layer is 30-60 nm (for example, it can be 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, and a range formed by any two of the above values ​​and a value within the range).

[0041] Preferably, the porosity of the porous support layer is 4-65%, preferably 45-55% (for example, it can be 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, and the range formed by any two of the above values ​​and the values ​​within the range).

[0042] Within the above range, it can be further ensured that the membrane with separation function can have higher magnesium-lithium separation efficiency and water flux when used for magnesium-lithium separation.

[0043] The present invention has no special requirements for the materials of the substrate layer, the porous support and the separation layer. However, preferably, the material of the substrate layer is selected from polyolefins (for example, polyethylene non-woven fabric).

[0044] According to the present invention, preferably, the film-forming polymer forming the porous support layer is selected from at least one of polyethersulfone, polysulfone, polyaromatic ether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryletherketone, preferably polyethersulfone and polysulfone; more preferably, the weight average molecular weight of the film-forming polymer forming the porous support layer is 50,000-100,000 g / mol (for example, it can be 50,000 g / mol, 60,000 g / mol, 70,000 g / mol, 80,000 g / mol, 90,000 g / mol, 100,000 g / mol).

[0045] According to the present invention, preferably, the film-forming polymer forming the separation layer is polyurea. The inventors of the present invention further found in their research that in the above case, the acid and alkali resistance of the membrane can be further guaranteed.

[0046] In a fifth aspect, the present invention provides a method for preparing a membrane having a separation function, the method comprising: introducing the modified lithium ion sieve as described in the first aspect or the third aspect into the process of preparing the membrane.

[0047] According to the present invention, preferably, the method further comprises: sequentially preparing a porous support layer and a separation layer on the substrate layer, and introducing the modified lithium ion sieve into the porous support layer during the preparation of the porous support layer.

[0048] According to the present invention, preferably, the material of the substrate layer is selected from polyolefins.

[0049] According to the present invention, preferably, the film-forming polymer forming the porous support layer is selected from at least one of polyethersulfone, polysulfone, polyaromatic ether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryletherketone, preferably polyethersulfone and polysulfone; more preferably, the weight average molecular weight of the film-forming polymer forming the porous support layer is 50,000-100,000 g / mol.

[0050] According to the present invention, preferably, the method further comprises: using a dispersion containing a film-forming polymer for forming a porous support layer and a modified lithium ion sieve to prepare a porous support layer on a substrate layer. In this way, a membrane loaded with a modified lithium ion sieve on the porous support layer can be prepared. The dispersant of the dispersion is not particularly limited, and can be, for example, N,N-dimethylformamide, N,N-dimethylacetamide, etc.

[0051] According to the present invention, preferably, in the dispersion, the mass concentration of the film-forming polymer used to form the porous support layer is 10-25wt%, more preferably 16-22wt% (for example, it can be 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt% and the range formed by any two of the above values ​​and the values ​​within the range).

[0052] According to the present invention, preferably, in the dispersion, the mass concentration of the modified lithium ion sieve is 0.0001-3wt%, preferably 0.05-2wt% (for example, it can be 0.05wt%, 0.1wt%, 0.3wt%, 0.5wt%, 1wt%, 1.2wt%, 1.5wt%, 2wt% and the range formed by any two of the above values ​​and the value within the range).

[0053] According to the present invention, preferably, in the dispersion, the mass concentration ratio of the film-forming polymer for forming the porous support layer to the modified lithium ion sieve is (6-400):1, preferably (100-360):1.

[0054] The film-forming polymer for forming the porous supporting layer and the modified lithium ion sieve may be dispersed in a dispersant, and then the obtained dispersion is allowed to stand at 22-28° C. for degassing for 2-4 hours.

[0055] According to the present invention, preferably, the method of preparing the porous support layer on the substrate layer includes: coating the dispersion liquid on the substrate layer (for example, it can be coated by a doctor blade), and then soaking the substrate layer coated with the dispersion liquid in water at 10-30° C. for 10-60 minutes. It can be understood that soaking can promote the formation of the porous support layer. After soaking, the material can also be washed with water.

[0056] According to the present invention, preferably, the conditions for preparing the porous support layer on the substrate layer include making the thickness of the porous support layer 10-100 μm, more preferably 30-60 μm. As above, relative to the thickness of the porous support layer, the average particle size of the modified lithium ion sieve is generally low (preferably, at the nanometer level). Therefore, the presence of the modified lithium ion sieve generally does not significantly affect the thickness of the porous support layer.

[0057] According to the present invention, preferably, relative to 1m 2 The amount of the modified lithium ion sieve is about 1-4000 mg, more preferably 60-1500 mg. The amount of the dispersion can be adjusted to meet the above range.

[0058] According to the present invention, preferably, the separation layer is prepared by forming the separation layer on the surface of the porous support layer by interfacial polymerization.

[0059] Preferably, the conditions for preparing the separation layer include making the thickness of the separation layer 80-110 nm.

[0060] According to the present invention, preferably, the interfacial polymerization method comprises: contacting the surface of the porous support layer with an aqueous solution containing polyamine and an organic solution containing polyisocyanate in sequence, and performing heat treatment. Through the above preparation method, a separation layer made of polyurea can be obtained.

[0061] Preferably, the polyamine is selected from at least one of m-phenylenediamine, p-phenylenediamine, o-phenylenediamine, 1,3,5-triaminobenzene, melamine, piperazine, diethylenetriamine, tetraethylenepentamine, polyethyleneimine and polyetheramine, more preferably polyethyleneimine and / or polyethylenepolyamine.

[0062] According to the present invention, preferably, in the aqueous solution containing polyamine, the mass concentration of the polyamine is 0.1-10wt%, more preferably 0.5-2.5wt% (for example, it can be 0.5wt%, 1wt%, 1.5wt%, 2.wt%, 2.5wt%, and the range formed by any two of the above values ​​and the value within the range).

[0063] According to the present invention, preferably, the polyisocyanate is selected from at least one of m-xylylene diisocyanate, isophorone diisocyanate, 1,6-hexamethylene diisocyanate, toluene-2,6-diisocyanate, 1,4-phenylene diisocyanate and toluene-2,4-diisocyanate, more preferably 1,4-phenylene diisocyanate and / or 1,6-hexamethylene diisocyanate.

[0064] According to the present invention, preferably, in the organic solution containing polyisocyanate, the mass concentration of the polyisocyanate is 0.01-2wt%, preferably 0.05-1wt% (for example, it can be 0.05wt%, 0.1wt%, 0.2wt%, 0.5wt%, 0.8wt%, 1wt% and the range formed by any two of the above values ​​and the value within the range).

[0065] According to the present invention, preferably, the ratio of the mass of the polyamine in the aqueous solution containing the polyamine to the mass of the polyisocyanate in the organic solution containing the polyisocyanate is (1-200):1, preferably (5-50):1.

[0066] The total amount of the polyamine in the aqueous solution containing the polyamine and the total amount of the polyisocyanate in the aqueous solution containing the polyisocyanate are not particularly limited, as long as the polyurea separation layer can be formed on the support layer. Generally, the amount of the above two is greater than the amount that can participate in the reaction to form the polyurea separation layer. For example, relative to 400 cm 2 The amount of the polyamine can be 5-500 mg, and the amount of the polyisocyanate can be 0.5-50 mg.

[0067] According to the present invention, preferably, the porous support layer is in contact with the aqueous solution containing the polyamine for 5-100 seconds, more preferably 10-60 seconds.

[0068] According to the present invention, preferably, the porous support layer is in contact with the organic phase containing the polyisocyanate for 10-200 s, more preferably 20-120 s.

[0069] The contact between the porous support layer and the aqueous solution containing polyamines, and the contact between the porous support layer and the organic phase containing polyisocyanates can be carried out at room temperature, such as 23-26°C.

[0070] According to the present invention, preferably, the heat treatment temperature is 40-150° C., preferably 50-120° C.; the heat treatment time is 0.5-10 min, more preferably 1-5 min.

[0071] Once prepared, the membrane can be soaked in water and is ready for use.

[0072] In a sixth aspect, the present invention provides a membrane with separation function prepared by the method described in the fifth aspect.

[0073] The membrane with separation function prepared by the above method has a higher water flux and magnesium-lithium separation efficiency when applied to magnesium-lithium separation, and has better acid and alkali resistance, and is more suitable for practical applications.

[0074] In a seventh aspect, the present invention provides the use of the membrane with separation function as described in the fourth aspect or the sixth aspect in magnesium-lithium separation.

[0075] The present invention will be described in detail below through examples.

[0076] Before interfacial polymerization is carried out on the porous support layer, the average pore size and porosity of the porous support layer are measured by a pore size analyzer (model PSDA-20, purchased from Nanjing Gaoqian) (the preparation of the separation layer generally does not affect the condition of the porous support layer that has been formed).

[0077] Preparation Example 1

[0078] Li4Ti5O 12 Ball milling was performed in a ball mill for 12 h to improve the dispersion. Then polyvinyl alcohol (weight average molecular weight of 20,000 g / mol), Li4Ti5O 12 (average particle size of 400nm) was mixed in ultrapure water so that the concentration of polyvinyl alcohol in the mixed material was 0.8wt% and the concentration of lithium ion sieve was 0.8wt%. The mixture was stirred and mixed at 30°C for 150min. The product was then centrifuged at room temperature and then washed three times with pure water. The product was ball-milled and dispersed at room temperature for 6h and dried (time 8h, temperature 80°C). The modified lithium ion sieve A was obtained.

[0079] Preparation Example 2

[0080] Li4Mn5O 12 Ball milling was performed for 12 h in a ball mill to improve the dispersion. Then polyvinyl alcohol (weight average molecular weight of 20,000 g / mol), Li4Mn5O 12 (average particle size of 500nm) was mixed in ultrapure water so that the concentration of polyvinyl alcohol in the mixture was 1.2wt% and the concentration of lithium ion sieve was 2.4wt%. The mixture was stirred at 35°C for 120min. The product was then centrifuged at room temperature and then washed three times with pure water. The product was dispersed by ball milling at room temperature for 6h and dried (time 9h, temperature 90°C). The modified lithium ion sieve B was obtained.

[0081] Preparation Example 3

[0082] The process was carried out in the same manner as in Preparation Example 1, except that the concentration of polyvinyl alcohol was 1.1 wt % and the concentration of lithium ion sieve was 0.5 wt % to obtain modified lithium ion sieve C.

[0083] Preparation Example 4

[0084] Li4Ti5O 12 Ball milling was performed in a ball mill for 12 h to improve the dispersion. Then polyvinyl alcohol (weight average molecular weight of 40,000 g / mol), Li4Ti5O 12 (average particle size of 400nm) was mixed in ultrapure water so that the concentration of polyvinyl alcohol in the mixture was 0.8wt% and the concentration of lithium ion sieve was 0.8wt%. The mixture was stirred at 30°C for 150min. The product was then centrifuged at room temperature and then washed three times with pure water. The product was dispersed by ball milling at room temperature for 6h and dried (time 8h, temperature 80°C). The modified lithium ion sieve D was obtained.

[0085] Preparation Example 5

[0086] Li4Ti5O 12 Ball milling was performed in a ball mill for 12 h to improve the dispersion. Then polyvinyl alcohol (weight average molecular weight of 20,000 g / mol), Li4Ti5O 12 (average particle size of 400nm) was mixed in ultrapure water so that the concentration of polyvinyl alcohol in the mixture was 4wt% and the concentration of lithium ion sieve was 0.8wt%. The mixture was stirred at 30℃ for 150min. The product was then centrifuged at room temperature and then washed three times with pure water. The product was dispersed by ball milling at room temperature for 6h and dried (time 8h, temperature 80℃). The modified lithium ion sieve E was obtained.

[0087] Preparation Example 6

[0088] The same as Preparation Example 1, except that polyvinyl alcohol was replaced by polyethylene glycol (weight average molecular weight of 400 g / mol), to obtain modified lithium ion sieve F.

[0089] Example 1

[0090] Using N,N-dimethylformamide as a dispersant, a porous support layer casting solution with a polysulfone (weight average molecular weight of 80,000 g / mol) concentration of 18wt% and a modified lithium ion sieve A concentration of 0.05wt% was prepared, and degassed at 25°C for 120min. Then, the casting solution was coated with a scraper (the volume of the casting solution coated was such that the volume of the casting solution was 100% relative to 1m 2 The substrate layer, the amount of lithium ion sieve is about 60 mg) is placed on a polyethylene non-woven fabric (thickness 75 μm, average pore size 18 μm, porosity 21%), which is then immersed in water at a temperature of 25°C for 60 minutes and then washed three times to form a porous supporting layer.

[0091] The upper surface of the porous support layer (area 400cm 2 ) is contacted with an aqueous solution (50 ml) containing 0.5 wt% polyethyleneimine, and the liquid is discharged after contacting at 25°C for 60 seconds; then, the upper surface of the support layer is contacted with an Isopar E solution (30 ml) containing 0.1 wt% 1,3-phenylene diisocyanate, and the liquid is discharged after contacting at 25°C for 60 seconds; then, the membrane is placed in an oven and heat treated at 70°C for 5 minutes.

[0092] Example 2

[0093] A membrane was prepared according to the method of Example 1, except that the concentration of modified lithium ion sieve A was 0.18 wt %.

[0094] Example 3

[0095] The membrane was prepared according to the method of Example 1, except that the concentration of modified lithium ion sieve A was 0.1 wt %.

[0096] Example 4

[0097] A membrane was prepared according to the method of Example 1, except that the concentration of modified lithium ion sieve A was 1.2 wt %.

[0098] Example 5

[0099] The membrane was prepared according to the method of Example 1, except that the modified lithium ion sieve A was replaced by the modified lithium ion sieve B.

[0100] Example 6

[0101] The membrane was prepared according to the method of Example 1, except that the modified lithium ion sieve A was replaced by modified lithium ion sieve C.

[0102] Example 7

[0103] The membrane was prepared according to the method of Example 1, except that the modified lithium ion sieve A was replaced by modified lithium ion sieve D.

[0104] Example 8

[0105] A membrane was prepared according to the method of Example 1, except that the concentration of polysulfone was 20 wt%.

[0106] Example 9

[0107] The membrane was prepared according to the method of Example 1, except that the modified lithium ion sieve A was replaced by modified lithium ion sieve E.

[0108] Example 10

[0109] The membrane was prepared according to the method of Example 1, except that the concentration of modified lithium ion sieve A was 3 wt %.

[0110] Embodiment 11

[0111] Using N,N-dimethylformamide as a dispersant, a porous support layer casting solution with a polysulfone (weight average molecular weight of 100,000 g / mol) concentration of 20wt% and a modified lithium ion sieve A concentration of 0.15wt% was prepared, and degassed at 25°C for 120min. Then, the casting solution was coated with a scraper (the amount of coating was such that relative to 1m 2 The substrate layer, the amount of lithium ion sieve is about 70 mg) is placed on a polyethylene non-woven fabric (thickness 85 μm, average pore size 15 μm, porosity 18%), which is then immersed in water at a temperature of 24°C for 50 minutes and then washed three times to form a porous supporting layer.

[0112] The upper surface of the porous support layer (area 400cm 2 ) was contacted with an aqueous solution (50 ml) containing 1.5 wt% polyethylene polyamine, and the liquid was drained after contacting at 25°C for 45 seconds; then, the upper surface of the support layer was contacted with an Isopar E solution (30 ml) containing 0.12 wt% 1,6-hexamethylene diisocyanate, and the liquid was drained after contacting at 25°C for 45 seconds; then, the membrane was placed in an oven and heat treated at 60°C for 3 minutes.

[0113] Example 12

[0114] Using N,N-dimethylformamide as a dispersant, a porous support layer casting solution with a polysulfone (weight average molecular weight of 80,000 g / mol) concentration of 19wt% and a modified lithium ion sieve A concentration of 0.2wt% was prepared, and degassed at 25°C for 120min. Then, the casting solution was coated with a scraper (the amount of coating was such that relative to 1m 2 The substrate layer, the amount of lithium ion sieve is about 50 mg) is placed on a polyethylene non-woven fabric (thickness 75 μm, average pore size 20 μm, porosity 25%), which is then immersed in water at a temperature of 26°C for 45 minutes and then washed three times to form a porous support layer.

[0115] The upper surface of the porous support layer (area 400cm 2 ) was contacted with an aqueous solution (50 ml) containing 1.0 wt% polyethyleneimine, and the liquid was drained after contacting at 25°C for 50 seconds; then, the upper surface of the support layer was contacted with an Isopar E solution (30 ml) containing 0.08 wt% of 1,3-phenylene diisocyanate, and the liquid was drained after contacting at 25°C for 80 seconds; then, the membrane was placed in an oven and heat treated at 80°C for 4 minutes.

[0116] Comparative Example 1

[0117] The membrane was prepared according to the method of Example 1, except that the porous support layer casting solution did not contain the modified lithium ion sieve A.

[0118] Comparative Example 2

[0119] The membrane was prepared according to the method of Example 1, except that the modified lithium ion sieve A was replaced by Li4Ti5O 12 .

[0120] Comparative Example 3

[0121] The membrane was prepared according to the method of Example 1, except that the modified lithium ion sieve A was replaced by modified lithium ion sieve F.

[0122] Among them, in Examples 2-10 and Comparative Examples 1-3, the volume of the casting liquid applied is consistent with that in Example 1.

[0123] Test Example 1

[0124] XPS was used to analyze the lithium ion sieve before and after modification. The change in C / O percentage came from the contribution of the polyvinyl alcohol coating layer, indicating that a polyvinyl alcohol coating layer was indeed formed on the modified lithium ion sieve.

[0125] Determine the mass content of polyvinyl alcohol in the modified lithium ion sieve (i.e., the mass content of polyvinyl alcohol in Table 1), and the specific method is the ratio of the weight gain after modification (i.e., the mass of polyvinyl alcohol) to the mass of the modified lithium ion sieve;

[0126] The average particle size of the modified lithium ion sieve was measured by transmission electron microscopy (TEM), and the average thickness of the polyvinyl alcohol was obtained by subtracting the average particle size of the lithium ion sieve from the average particle size of the modified lithium ion sieve.

[0127] Table 1

[0128]

[0129] Test Example 2

[0130] The films prepared in the above embodiments and comparative examples were tested as follows:

[0131] The loading amount of the modified lithium ion sieve relative to 1 g of the membrane (i.e., the loading amount of the modified lithium ion sieve in Table 2) was determined by X-ray photoelectron spectroscopy (XPS);

[0132] The thickness of the porous support layer and the separation layer was measured using scanning electron microscopy.

[0133] Table 2

[0134]

[0135]

[0136] Test Example 3

[0137] After the membranes obtained in the above examples and comparative examples were immersed in water for 24 hours, the water flux and the desalination rate of magnesium chloride and lithium chloride were measured. The specific method is as follows.

[0138] The membrane was placed in the membrane pool, and the water permeation of the membrane was measured at 0.5 MPA and 25 °C within a certain period of time, and the water flux was calculated by the following formula:

[0139] J = Q / (A·t), where J is the water flux, Q is the water permeation (L), and A is the effective membrane area of ​​the composite nanofiltration membrane (m 2 ), t is time (h);

[0140] (2) The desalination rate of the composite nanofiltration membrane was tested by the following method: the composite nanofiltration membrane was placed in a membrane pool, and a 2000 ppm magnesium chloride aqueous solution and a 100 ppm lithium chloride aqueous solution were respectively pre-pressed at 0.5 MPa for 0.5 h, and then the permeate was obtained at a pressure of 0.6 MPa. The concentrations of magnesium chloride and lithium chloride in the permeate were measured by ion chromatography, and the desalination rate was calculated by the following formula:

[0141] R = (Cp-Cf) / Cp×100%, where R is the desalination rate, Cp is the concentration of magnesium chloride or lithium chloride in the stock solution (measured by ion chromatography), and Cf is the concentration of magnesium chloride or lithium chloride in the permeate (measured by ion chromatography);

[0142] (3) The magnesium-lithium separation coefficient of the composite nanofiltration membrane was tested by the following method: the composite nanofiltration membrane was placed in a membrane pool, the original aqueous solution was a mixed aqueous solution of 2000 ppm magnesium chloride and 100 ppm lithium chloride, the aqueous solution was pre-pressed at 0.5 MPa for 0.5 h, and then a permeate was obtained at a pressure of 0.6 MPa. The concentrations of magnesium chloride and lithium chloride in the permeate were measured by ion chromatography, and the desalination rate was calculated by the following formula:

[0143] The lithium-magnesium separation coefficient is calculated by the following formula:

[0144]

[0145] Where S is the lithium-magnesium separation coefficient, C Li,p and C Li,f are the concentrations of lithium ions in the permeate and raw material solution (measured by ion chromatography); C Mg,p and C Mg,f are the concentrations of magnesium ions in the permeate and raw solution (measured by ion chromatography), respectively.

[0146] Table 3

[0147]

[0148] After the membrane was immersed in a 20 wt % HCl aqueous solution for 480 h, the water flux and the desalination rate of magnesium chloride and lithium chloride were measured according to the above method. The results are shown in Table 4.

[0149] Table 4

[0150]

[0151] As can be seen from the table above, compared with the comparative example, the lithium permeability of the embodiment is increased, and the water flux is increased. The modified lithium ion sieve in the porous support layer has holes that match the size of lithium ions. With the cooperation of the above layers, it can provide a specific channel for lithium ions, while magnesium ions cannot pass through, and lithium ions can specifically and quickly pass through the membrane under the pressure of the circulating water, which improves the retention rate of the membrane for multivalent metal cations, and at the same time allows lithium ions to pass as quickly as possible, the membrane has a large flux, and has a high magnesium-lithium separation efficiency.

[0152] In addition, the inventors of the present invention also found that after the nanofiltration membrane was soaked in acid for 480 hours, the XPS characterization of the loading amount of the modified lithium ion sieve in the membrane prepared in Examples 1-12 was within the range of ±0.2%, and it can be basically considered that the modified lithium ion sieve did not fall off, indicating that the modified lithium ion sieve loaded on the porous support layer of the membrane provided by the present invention is more stable and more suitable for practical use. The membrane prepared in Comparative Example 2, the XPS characterization of the loading amount of the lithium ion sieve changed by 6wt% (reduction).

[0153] Furthermore, it can be seen from Table 4 that the membrane provided by the present invention has substantially no change in its lithium ion permeability after being soaked in 5wt% HCl for 480 hours, indicating that the membrane and the polyurea separation layer thereon have strong acid and alkali resistance. The membrane can achieve separation of monovalent lithium metal ions and high-valent metal ions (such as magnesium) under acidic conditions.

[0154] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A modified lithium ion sieve, characterized in that: The modified lithium ion sieve comprises a lithium ion sieve and polyvinyl alcohol coating the lithium ion sieve, wherein the mass content of the polyvinyl alcohol is 0.5-5wt% relative to the mass of the modified lithium ion sieve.

2. The modified lithium ion sieve according to claim 1, wherein Relative to the total mass of the modified lithium ion sieve, the mass content of polyvinyl alcohol is 0.9-2.5wt%; and / or, the average thickness of the polyvinyl alcohol coating the lithium ion sieve is 1-20 nm, preferably 2-8 nm; And / or, the average particle size of the modified lithium ion sieve is 10 nm-10 μm, more preferably 20-520 nm.

3. The modified lithium ion sieve according to claim 1 or 2, wherein: The lithium ion sieve is selected from a lithium manganese oxide type lithium ion sieve and / or a lithium titanium oxide type lithium ion sieve; And / or, the weight average molecular weight of the polyvinyl alcohol is 20,000-40,000 g / mol.

4. A method for preparing a modified lithium ion sieve, characterized in that: The method comprises: mixing polyvinyl alcohol and lithium ion sieve in a solution state to obtain a modified lithium ion sieve, wherein the mass ratio of the lithium ion sieve to the polyvinyl alcohol is (0.3-5):

1.

5. The method according to claim 4, wherein: The mass ratio of polyvinyl alcohol and lithium ion sieve is (0.4-2):1; and / or, in the solution, the mass concentration of polyvinyl alcohol is 0.1-5wt%; and / or, the mixing time is 2-4 hours and the mixing temperature is 20-40° C.; and / or, the average particle size of the lithium ion sieve is 10 nm-10 μm, more preferably 20-500 nm; And / or, the lithium ion sieve is selected from a lithium manganese oxide type lithium ion sieve and / or a lithium titanium oxide type lithium ion sieve; And / or, the weight average molecular weight of the polyvinyl alcohol is 20,000-40,000 g / mol; And / or, the method further comprises: performing solid-liquid separation on the mixed materials. The obtained solid phase material is dried.

6. The modified lithium ion sieve prepared by the method according to claim 4 or 5.

7. A membrane having a separation function, characterized in that: The membrane with separation function comprises a porous support layer, a separation layer and the modified lithium ion sieve according to any one of claims 1 to 3 and claim 6 further loaded on the porous support layer and / or the separation layer.

8. The membrane having separation function according to claim 7, wherein: Relative to 1g of the membrane, the loading amount of the modified lithium ion sieve is 1-100mg, preferably 3-15mg; And / or, the membrane with separation function comprises a substrate layer, a porous support layer and a separation layer in sequence, and the modified lithium ion sieve is loaded on the porous support layer.

9. The membrane having separation function according to claim 8, wherein: The thickness of the substrate layer is 30-150 μm, preferably 50-120 μm; the average pore diameter is 10-25 μm; and the porosity is 15-25%; and / or, the thickness of the porous support layer is 10-100 μm, preferably 30-60 μm; and / or, the separation layer has a thickness of 80-110 nm, preferably 85-95 nm; And / or, the average pore size of the porous support layer is 30-60 nm; And / or, the porosity of the porous support layer is 4-65%, preferably 45-55%.

10. The membrane having separation function according to claim 8 or 9, wherein: The material of the substrate layer is selected from polyolefin; and / or, the film-forming polymer forming the porous support layer is selected from at least one of polyethersulfone, polysulfone, polyarylether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryletherketone, preferably polyethersulfone and polysulfone; more preferably, the weight average molecular weight of the film-forming polymer forming the porous support layer is 50,000-100,000 g / mol; And / or, the film-forming polymer forming the separation layer is polyurea.

11. A method for preparing a membrane having a separation function, characterized in that: The method comprises: introducing the modified lithium ion sieve described in any one of claims 1 to 3 and claim 6 into the process of preparing the membrane.

12. The method according to claim 11, wherein: The method further comprises: sequentially preparing a porous support layer and a separation layer on the substrate layer, and introducing the modified lithium ion sieve into the porous support layer during the preparation of the porous support layer; And / or, the material of the substrate layer is selected from polyolefins; and / or, the film-forming polymer forming the porous support layer is selected from at least one of polyethersulfone, polysulfone, polyarylether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryletherketone, preferably polyethersulfone and polysulfone; more preferably, the weight average molecular weight of the film-forming polymer forming the porous support layer is 50,000-100,000 g / mol; Preferably, the method further comprises: preparing a porous support layer on the substrate layer using a dispersion containing a film-forming polymer for forming a porous support layer and a modified lithium ion sieve; Preferably, in the dispersion, the mass concentration of the film-forming polymer used to form the porous support layer is 10-25wt%, preferably 16-22wt%; Preferably, in the dispersion, the mass concentration of the modified lithium ion sieve is 0.0001-3wt%, preferably 0.05-2wt%; Preferably, in the dispersion, the mass concentration ratio of the film-forming polymer used to form the porous support layer to the modified lithium ion sieve is (6-400):1, preferably (100-360):1; Preferably, the method of preparing the porous support layer on the substrate layer comprises: coating the dispersion on the substrate layer, and then soaking the substrate layer coated with the dispersion in water at 10-30° C. for 10-60 min; Preferably, the conditions for preparing the porous supporting layer on the substrate layer include making the thickness of the porous supporting layer 10-100 μm, preferably 30-60 μm.

13. The method according to claim 12, wherein: The method of preparing the separation layer is as follows: forming the separation layer on the surface of the porous support layer by interfacial polymerization; And / or, the conditions for preparing the separation layer include making the thickness of the separation layer 80-110 nm.

14. The method according to claim 13, wherein: The interfacial polymerization method includes: contacting the surface of the porous support layer with an aqueous solution containing polyamine and an organic solution containing polyisocyanate in sequence, and performing heat treatment; Preferably, the polyamine is selected from at least one of m-phenylenediamine, p-phenylenediamine, o-phenylenediamine, 1,3,5-triaminobenzene, melamine, piperazine, diethylenetriamine, tetraethylenepentamine, polyethyleneimine and polyetheramine, more preferably polyethyleneimine and / or polyethylenepolyamine; Preferably, in the aqueous solution containing polyamine, the mass concentration of the polyamine is 0.1-10wt%, preferably 0.5-2.5wt%; Preferably, the polyisocyanate is selected from at least one of m-xylylene diisocyanate, isophorone diisocyanate, 1,6-hexamethylene diisocyanate, toluene-2,6-diisocyanate, 1,4-phenylene diisocyanate and toluene-2,4-diisocyanate, more preferably 1,4-phenylene diisocyanate and / or 1,6-hexamethylene diisocyanate; Preferably, in the organic solution containing polyisocyanate, the mass concentration of polyisocyanate is 0.01-2wt%, preferably 0.05-1wt%; Preferably, the ratio of the mass of the polyamine in the aqueous solution containing the polyamine to the mass of the polyisocyanate in the organic solution containing the polyisocyanate is (1-200):1, preferably (5-50):1; Preferably, the porous support layer is in contact with the aqueous solution containing the polyamine for 5-100 s, preferably 10-60 s; Preferably, the porous support layer is in contact with the organic phase containing the polyisocyanate for 10-200 s, preferably 20-120 s; Preferably, the heat treatment temperature is 40-150° C., preferably 50-120° C.; the heat treatment time is 0.5-10 min, preferably 1-5 min.

15. A membrane with separation function prepared by the method according to any one of claims 11 to 14.

16. Use of the membrane with separation function as claimed in claim 7 or claim 15 in magnesium-lithium separation.

Citation Information

Patent Citations

  • Granular lithium ion sieve

    CN101955210A

  • Preparation method of chromium removal composite ion sieve

    CN102814170A

  • Lithium-ion permselective membrane and preparation method thereof

    CN105903361A

  • Preparation method of composite adsorbent and method for extracting lithium from brine

    CN109225121A

  • Acid / alkali-resistant composite nanofiltration membrane as well as preparation method and application thereof

    CN113509839A

Cited By

  • Granular manganese adsorbent as well as preparation method and application thereof

    CN120169328A